ڕەوشی ئێران لە سايەی ململانێ لەسەر جێنشينى تەيمور و دەركەوتنى شاهروخ (807-814ك/1405-1412ز) - زەينەڵ, پ. د. ئاراس فەريق; محمد, هێشو صەلاح (Sulaimani Journal for Humanities, 2023)
Timur ruled over a large empire during his reign and every state or territory was ruled by one of his sons (Amirs) and descendants (Amirzadehs). Timur himself appointed his successor to the empire before his death for the sake of protecting geographic border and preventing emergence of internal conflict among his family but after Timur's illness and death there was a fierce conflict among Timur's sons and descendants to overcome his rivals and take the throne. Even appointing a successor by Timur himself could not prevent those conflicts. Also, because of the division Timur had made before his death among his sons and grandchildren caused every one of them to possess their own position and power and this facilitated further widening the conflict and not admitting to each other's power. The consequences of this internal conflict among Timur's family on their geographical territories appeared very soon, exclusively in Iran. This conflict made Khorasan, Astrabad, Fars, Sistan, Azerbaijan and other territories the main field to resolve Timurid Amirs' and Amirzadehs' supremacy, which eventually ended with Shahrukh’s son of Timur's victory. He was the ruler of the Timorid Empire for nearly 45 years.